Olive of Groves - Nannestad, Katrina (ABC books / HarperCollins Publishers Australia, 2015)
Olive has always dreamed of attending boarding school, but Mrs Groves' Boarding School for Naughty Boys, Talking Animals and Circus Performers is not what she expected. To tell the truth, dear reader, it is not what anyone expected! The headmistress is completely bonkers and Pig McKenzie, school bully and all-round nasty swine, is determined to make Olive's life unbearable. Olive, however, is clever, sweet and kind, and soon gains the loyalty and devotion of three rats, a short-sighted moose, a compulsive liar and a goose who faints at the sight of cherries. But will friendship and wits be enough when Pig McKenzie puts his Truly Wicked Plan into gear? Or will Olive be cast out of Groves forever?
Keywords: Boarding schools / Juvenile fiction; Circus / Juvenile fiction; Grandparent and child / Juvenile fiction; Australian fiction; Boarding schools; Circus; Grandparent and child; Fiction; Juvenile works; Kinderbuch